Hygienic features of chemical air pollution in aluminum production - N. M. Meshchakova; S. F. Shayakhmetov; L. G. Lisetskaya; A. V. Merinov; O. L. Kalinina (Acta Biomedica Scientifica, 2016)
The article presents retrospective assessment of chemical factors in aluminum production over a long follow-up period. The main pollutants of the workplace air are fluorine compounds, resinous substances, and disintegration aerosol. The comparative assessment of the workplace air composition during the operation of electrolytic cells with self-baking anodes and when using a new technology with pre-baked anodes was carried out. The results of the research were processed using standard parametric methods of calculation of mean value and error in mean. It is shown that the introduction of a new technology of pre-baked anodes contributes to the optimization of working environment, reduction of harmful chemicals in the workplace air.